Practicing catching-up: A comparison of development models of East Asian and Central-Eastern European countries - Eric Terk (OrdnungsPolitisches Portal (OPO), 2014)
This article makes an attempt to compare the development patterns of the economies of the East Asian and Central and Eastern European (CEE) regions, which have been the fastest in catching up on the global arena. It observes both the internal fea-tures of the economies and economic policies and the parameters characterising their relation with the international background (openness, integration).The statistical materials used have been taken mostly from the World Economic Forum competi-tiveness reports and from the WB and IMF sources, while the descriptions of eco-nomic policy and its dynamic are based on materials concerning the regions under discussion and their individual countries. The goal of the article is not to reach con-clusions characterising the behaviour of the economies of the entire East Asian or CEE regions, but the economic development models, specific features, development and performing of countries, which have displayed top performance in either region and have reached the level of developed economies.
Keywords: 330; catching up; development models; developmental state